Tudo isso era maré: origens, consolidação e erradicação de uma favela de palafitas em São Luís do Maranhão - Joana Barbosa Vieira da Silva (2016)
In order to reveal the specificities of a brazilian stilt-house slum, a historical reconstruction of the expansion process was made. In mangrove, such territory was produced autonomously by the residents, away from the eyes and interests of dominant economic and political institutions. In recent years, however, a slum upgrading program is being implemented in the area. The origins of the territory date back to the late nineteenth century. The first chapter, origins, was made through the use of city plans, official documents, linked to literary writings, chronicles and press reports. The consolidation period had residents as protagonists, who told in the first person their experience of building the houses in the mangrove. That chapter also integrates aerial photographs and satellite images that allowed to identify the morphology of the expansion process. Finally, the eradication observes the present time, where a cut to the previous phases is made by the upgrading project, intended to deconstruct what had been produced by the community. By realizing the specificities of the territory, it is concluded that the way slum upgrading program was implemented, contributed to reduce the autonomy of residents and thus had deepened inequalities. There are alternative ways for such programs, not by suppressing what exists but by valuing local resources, adopting solutions that can begin with the recognition of stilt-houses as a constructive and spatial culture.